MPPT controller for a solar PV array with temperature-compensated P&O algorithm - Abdulaziz H. Yusuf; Ceyda Aksoy Tirmikci; Eltahir Idris Eltahir Mohamed (Bulletin of Electrical Engineering and Informatics, 2026)
Photovoltaic (PV) systems must operate at the maximum power point (MPP) to maintain efficiency under varying environmental conditions. This study develops a temperature-compensated perturb-and-observe (PO), maximum power point tracking (MPPT) controller integrated with a boost converter in MATLAB. A 100 kW PV array was modeled using realistic module parameters; baseline experiments without MPPT revealed power losses up to 70% and incorrect power–temperature correlations due to fixed-duty cycle operation. With MPPT enabled, the controller dynamically adjusted the duty ratio, achieving proportional scaling with irradiance and an inversely proportional response to temperature. Results confirm a peak summer output of 48.78 kW compared to 15 kW without MPPT, improving annual energy yield by a factor of three under realistic Sakarya operating conditions.